The Economic Law of Market Areas - Fetter, Frank A. (Quarterly Journal of Economics, 1924)
The Economic Law of Market Areas Frank A. Fetter Frank A. Fetter Princeton University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 38, Issue 3, May 1924, Pages 520–529, https://doi.org/10.2307/1882335 Published: 01 May 1924